Agrochemical Properties of Dry Soils of the Northern Part of Turkestan Ridge (Texas Journal of Agriculture and Biological Sciences, 2022)
The article analyzes the agrochemical properties of developed and undeveloped typical gray soils in the northern part of the Turkestan Range. The article analyzes the agrochemical properties of developed and undeveloped dry gray soils in the northern part of the Turkestan Range. In the undeveloped rainfed typical serozems of the Zaamin district of the Jizzakh region, the content of humus in the upper layer was 1.01-1.44%, gross nitrogen in the upper layers 0.072-0.124%, gross phosphorus 0.136-0.235%, mobile form 64.5-72.0 mg kg, total amount of potassium 1.10-1.24%, amount of exchangeable potassium 458-495 mg kg, and with developed typical gray soils, the content of humus in the upper layers is 0.62-0.97%, and gross nitrogen is 0.042-0.090%, the total amount of phosphorus is 0.104-0.128%, the mobile form is 25.6- 36.0 mg kg, the total amount potassium 0.90-0.96%, the amount of exchangeable potassium 241-361 mg kg, a decrease was observed towards the lower layers.